1999
DOI: 10.1016/s0017-9310(99)00059-9
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Rayleigh–Bénard convection in low Prandtl–number fluids

Abstract: An experimental investigation of Rayleigh-Blmard convection in liquid sodium has been performed in cylindrical test cells with aspect ratios between 20 and 4.6 for a range of Rayleigh numbers 1 04< Ra< 5 · 106. The Prandtl number is between 6.0·10-2+0.1·10-3. For low Rayleigh number Ra<104the dimensionless heatflux, Nu, is mainly conduction controlled and close to 1; a correlation Nu= 0.115 Ra0.25 describes the observations adequately for 2·104 < Ra < 5·106. lt is shown that the Nusselt numbers are smaller for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
1
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 50 publications
11
53
1
1
Order By: Relevance
“…In some recent experiments, however, Ciliberto, Cioni & Laroche (1996) have found that the Nusselt number in water does not change when screens are placed inside the domain so that the recirculation cell is destroyed. This would suggest that in the high P r regime the large-scale motion is ineffective in the heat Kerr (1996) at P r = 0.7; •, experimental results by Cioni et al (1997) at P r = 0.025; , experimental results by Cioni et al (1997) and by Chillá et al (1993) at P r = 4.0; , experimental results by Horanyi et al (1997) at P r = 0.005; , fit Nu ∼ Ra 0.285 ; , fit Nu ∼ Ra 0.25 ; , fit Nu ∼ Ra 0.25 . (b) Nu vs. P r relation at Ra = 6 × 10 5 :…”
Section: Resultsmentioning
confidence: 99%
“…In some recent experiments, however, Ciliberto, Cioni & Laroche (1996) have found that the Nusselt number in water does not change when screens are placed inside the domain so that the recirculation cell is destroyed. This would suggest that in the high P r regime the large-scale motion is ineffective in the heat Kerr (1996) at P r = 0.7; •, experimental results by Cioni et al (1997) at P r = 0.025; , experimental results by Cioni et al (1997) and by Chillá et al (1993) at P r = 4.0; , experimental results by Horanyi et al (1997) at P r = 0.005; , fit Nu ∼ Ra 0.285 ; , fit Nu ∼ Ra 0.25 ; , fit Nu ∼ Ra 0.25 . (b) Nu vs. P r relation at Ra = 6 × 10 5 :…”
Section: Resultsmentioning
confidence: 99%
“…This difference has been observed previously (e.g., refs. 23,25,34,36). The inertial scaling illustrates the dominant role of interior turbulence in liquid metal convection.…”
Section: Methodsmentioning
confidence: 95%
“…23,25,36). Essentially, the difference between scaling laws [1] and [4] is that in the former the thermal boundary layer thickness is determined by its own marginal stability, whereas in the latter the thermal boundary layer thickness is set by the strength of interior turbulence.…”
Section: Heat Transfer Regimesmentioning
confidence: 99%
“…As shown in Figure 7d, this large-scale axisymmetric, inertial circulation (with power dominantly at m = 0 and subdominantly at m = 4) generates similarly strong horizontal temperature gradients on the mid-plane of the fluid, again, approaching 60% of the imposed vertical temperature gradient. The decrease in dominant horizontal mode number from m = 3 in case RBC 1 n to the axisymmetric mode in case RBC 2 n is reminiscent of the inferred change in mode number in the Γ = 4.5 liquid sodium convection study of [53]. n , which has the highest Ra value and relatively low aspect ratio of Γ = 2, yields a classical large-scale circulation (LSC), with a single non-axisymmetric m = 1 inertial cell dominating the fluid domain [55][56][57].…”
Section: Resultsmentioning
confidence: 79%
“…In fact, experiments in liquid metals have yielded a wide range of results providing α values from 1/5 up to 1/3 [18,20,[51][52][53][54]. This broad range of possible α values shows that heat transfer in liquid metals is not as well understood as it is in moderate P r fluids [16].…”
Section: Essential Theorymentioning
confidence: 99%